HIV/AIDS Education in Health Professionals Training in the Philippines - Tawasil, John R. (Washington, DC, 2012)
It is recognized by both private and public sectors that an adequate education plays an important part in stemming the spread of HIV. While the topic of sex education among primary and secondary schools remains a contentious issue for a predominantly Catholic country like the Philippines, teaching health professionals about HIV/AIDS is a vital part of the subject of infectious diseases. At present, there is a need to evaluate the current curriculum of health professionals in terms of the adequacy of the teaching about HIV/AIDS. This study was undertaken to review the present state of HIV/AIDS education in undergraduate health professionals' curriculum and to assess the response of local tertiary private hospitals to the emerging threat of HIV/AIDS. It analyzes the current situation of HIV/AIDS lectures and discussions in public tertiary education academic curricula of health professionals in the Philippines. It determines the perceptions of different stakeholders as to the sufficiency of the current level of lectures and discussions on HIV/AIDS. It describes the private hospital sector response to the HIV/AIDS problem. This study was divided into two parts. The first part dealt with the first and second objectives, focusing on the training of health professionals for HIV/AIDS. The second part dealt with the third objective, investigating the response of the private sector to the HIV/AIDS problem.